Specific Gravity Analysis of Onion Peel and Snail Shell Particulates as Composite Fillers in Ship Applications - Sunday Ayoola Oke (Institut Teknologi Sepuluh Nopember, 2021)
There is limited knowledge on the specific gravity of agro-based fillers, particularly particulate onion peels and snail shells despite their potentials as the ship's hull composite materials. This work reports experimental results on specific gravity concerning particulate onion peels and snail shells as fillers in ship's hull composite fabrication. Specific gravity bottles, water, and 15g each of particulate onion peels, snail shells, and their mixtures were used in laboratory conditions. It was found that onion peel particulates (specific gravity of 1.09± 0.41 for 0.063 mm), snail shell particulates (specific gravity of 0.95 ± 0.01 for 0.063 mm), and mixtures of particulate onion peel and snail shell (specific gravity of 1.02 ± 0.08 for 0.150 mm, 10g particulate onion peels + 5g particulate snail shell) yielded the least values, requiring the least fuel expenditure in generating torque for the desired motions during the ship's voyage. Moreover, a policy to use the snail shell recommendation should be formulated as it is the overall best to help in cost reduction by shipping organizations. Previous studies were on tomatoes and potatoes, among others. However, the present study takes a new direction to innovatively consider hardly studied fillers for polymer composites for the first time.